Multi-year variability of summer phytoplankton biomass and size structure in the northern Chukchi and East Siberian Seas, Arctic Ocean: role of light and nutrient availability - Lee, Youngju; Cho, Kyoung-Ho; Jung, Jinyoung; Moon, Jong Kuk; Yang, Eun Jin; Kang, Sung-Ho (Frontiers in Marine Science, 2023)
In the Arctic Ocean, the northern Chukchi and East Siberian Seas (NCESS) are vulnerable to climate change due to warming, sea ice melting, and surface freshening. To investigate how local physical forcing affects phytoplankton biomass and communities in this area, the multi-year (2015-2020) distributions of summer (August) chlorophyll-a concentrations and size structures using data collected by the Korea-Arctic Ocean Observing System (K-AOOS) program were investigated. The environmental characteristics and phytoplankton communities in the study area showed east-west regional differences. It is characterized by warm fresh waters and strong stratification to the east and cold saline waters and relatively high nutrient and sea ice concentrations to the west. Despite the differences between the east and west regions, patterns of the inter-annual variation in phytoplankton biomass and communities were similar across the entire study area, implying environmental controllers regulating phytoplankton in the NCESS. Inter-annually, higher sea surface salinity and weaker water column stratification were observed in 2017-2019 than in 2015 and 2020, implying the possibility of a potential modulation by the Arctic Oscillation. The shallower nitracline depth and higher surface nutrient concentrations since 2017 compared to the period from 2015-2016, indicate improved nutrient availability due to Atlantic water intrusion. However, average insolation has been relatively low since 2017, with the exception of August 2018. August mean phytoplankton biomass was highest in 2018 in the study area (average 83.7 mgm -2 ) and was dominated by large-sized phytoplankton. The low phytoplankton biomass in 2017 (23.9 mgm -2 ) and 2019 (62.4 mgm -2 ), despite similar characteristics of nutrient concentration to 2018, is likely due to lower average daily insolation in both years (206 μEm -2 d -1 and 184 μEm -2 d -1 in 2017 and 2019, respectively) compared to the 2018 average (271 μEm -2 d -1 ). These results suggest that increased intrusion through upwelling of Atlantic water, along with nutrient loading, could be a pivotal driving factor contributing to this enhanced production in the NCESS, particularly under conditions where light levels are sufficient for phytoplankton growth and bloom development.